Systematic review of primary total hip arthroplasty using titanium-titanium modular-neck prostheses: the true risk of revision. Issue 3 (May 2021) - Lex, Johnathan R; Welch, Matthew D; See, Abbas; Edwards, Thomas C; Stavropoulos, Nikolaos A; Babis, George C
Aims: Modular-neck femoral implants are used to enable more variability in femoral neck version, offset and length. It has been reported that these implants carry a higher rate of revision. The aim of this review was to assess the overall and cause-specific revision rate of titanium-titanium alloy modular-neck implants in primary total hip arthroplasty (THA). Methods: A systematic review was conducted following PRISMA guidelines and utilising multiple databases. All results were screened for eligibility. Studies published from 2000 onwards, using a current-generation, titanium-titanium, modular-neck implant were included. Overall and cause-specific revision rates were analysed, comparing to fixed-neck prostheses where applicable. Results: 920 studies were screened. After applying exclusion criteria, 23 were assessed in full and 14 included. These consisted of 12 case series and 2 joint registry analyses. 21, 841 patients underwent a modular-neck implant with a weighted mean follow-up of 5.7 years, mean age of 62.4 years, and average body mass index (BMI) of 28.4kg/m 2 . The overall revision rate was 3.95% and 2.98% for modular and fixed-neck prostheses, respectively. For studies with >5 years follow-up the mean revision rate was 3.08%. There was no difference in cause-specific revision rates by implant design. Mean improvement in Harris Hip Score was 41.9. Conclusions: At medium-term, revision rates for titanium-titanium primary modular-neck THA are acceptable. These prostheses are a sensible management option in patients with considerable anatomical hip deformity not amenable to correction with standard fixed-neck implants. Patients of male gender, high BMI and requiring prostheses with a larger neck, offset or head are at higher risk of implant failure.